2022
DOI: 10.1155/2022/3528786
|View full text |Cite|
|
Sign up to set email alerts
|

The Current Status of SSRP1 in Cancer: Tribulation and Road Ahead

Abstract: Background and Objectives. Owing to the complexity and heterogeneity of tumors, cancer’s early diagnoses and treatment have become a provocation. Structure-specific recognition protein-1 (SSRP1) is a histone (H3-H4 or H2A-H2B) chaperone in chromatin-related processes such as transcription, cell cycle control, and DNA replication, reported in various tumor tissues. It may also be used as a biomarker. This study aimed to highlight the role of SSRP1 in cancer with a focus on the current progress and future perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Moreover, the levels of SSRP1 are notably higher in patients with high-grade glioma compared to those with low-grade glioma. 35 These findings indicate that SSRP1 may play a critical role in the progression of GBM. To further elucidate the involvement of SSRP1 in the advancement of GBM cells, various techniques, such as CCK-8 and EdU assays, as well as FACS analysis, have been employed.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the levels of SSRP1 are notably higher in patients with high-grade glioma compared to those with low-grade glioma. 35 These findings indicate that SSRP1 may play a critical role in the progression of GBM. To further elucidate the involvement of SSRP1 in the advancement of GBM cells, various techniques, such as CCK-8 and EdU assays, as well as FACS analysis, have been employed.…”
Section: Discussionmentioning
confidence: 84%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Facilitates chromatin transcription (FACT) is a histone chaperone involved in replication, transcription, chromatin reorganisation, DNA damage repair and cell fate determination [228][229][230][231] . It can bind to all core histones 228 and potentially several noncanonical histones 231 .…”
Section: Facilitates Chromatin Transcriptionmentioning
confidence: 99%